Editorial introduction: Islam, culture and women - Firdous, Azim (© 2011 Inter-Asia Cultural Studies, 2018)
This Editorial was published in the Inter-Asia Cultural Studies and the definite version is available at: http://doi.org/10.1080/14649373.2011.554646 The Journal's website is at: https://www.tandfonline.com/doi/abs/10.1080/14649373.2011.554646